Supporting Secondary Teachers’ Critical Disciplinary Literacies - Dyches, Jeanne (Open textbook library.)
Co-created with students in the course EDUC 395: Teaching Disciplinary Literacy and supported by CDL experts, this textbook offers accessible, research-based, multidisciplinary CDL strategies ready for implementation in secondary classrooms.